The pronunciation of English low vowels by Iraqi EFL learners : an intralingual analysis - Al Abdely, Ammar A. (Penerbit Universiti Kebangsaan Malaysia, 2021)
Iraqi EFL learners of English are reported to show accented pronunciation on the segmental level, which might affect their speech intelligibility. This study aimed to identify problems encountered by Iraqi EFL learners in the production of English low vowels and account for them from an intralingual perspective. The study also aimed to identify the effect of Iraqis' English language proficiency level on their pronunciation of English low vowels. Thus, learners were divided into beginners and advanced groups to determine differences between them based on their proficiency level in English. A production test was conducted to identify error patterns of twenty Iraqi EFL learners in producing low vowels. Learners’ recordings were acoustically analysed to validate the difficulties identified via the production test. Independent-samples ttests were conducted to identify any significant differences in performance for the two groups. The results showed that learners encountered problems in the production of low vowels, especially /ɒ/, /æ/ and /ʌ/. The study concluded that these problems are probably ascribed to the complexities of the L2 vowel space, where vowels are close to each other and thus difficult to produce. Significant differences were identified between the two groups in terms of error means. Nonetheless, the comparison between the vowel chart obtained in this study and the charts offered in previous studies revealed that Iraqi EFL learners are still far from attaining approximant pronunciation. This requires reconsidering current texts, methodologies, and techniques used in teaching English pronunciation to allocate more attention to spectral differences among vowels.